USLUB AL-QUR’AN DALAM AYAT-AYAT TENTANG SURGA - Khairul Fuadi; Ria Rafita Supriani (AL MA'ANY, 2022)
The language structure in the Qur'an has more advantages when compared to Arabic structures in general. This structure is a means of distinguishing from ordinary Arabic which gives rise to the meaning of majaz (in the science of bayan). The language style displayed in the Qur'an is also different from the language style of ordinary expressions. This is all part of the excellence (I'jaz) of the Qur'an. This problem is at least reflected in various opinions which state that the language of the Qur'an has advantages, uniqueness, beauty, and distinctiveness that are different from languages ​​other than the Qur'an. By looking at the language and literature in the Qur'an, in this journal the author will discuss the forms of sentences used to describe something. These sentences are not ordinary sentences (based on language structure alone), but sentences that come out of the structure or language used in communication. As for what is included in this discussion, the author limits it to a few aspects, such as al-Taqdîm wa al-Ta'khîr, Tasybîh, Isti'ârah and Kinâyah especially in verses about heaven. The method used in writing this journal is descriptive analysis method. Data collection in this study was carried out by reviewing or exploring several journals, books and documents (both printed and electronic) as well as other sources of data or information deemed relevant to research or study. al-Taqdîm wa al-Ta'khîr which aims to ikhtishash, Tasybîh which aims at parables, Isti'ârah which aims to borrow, meaning to use a pronunciation that is not in accordance with its original meaning, and Kinâyah which aims to explain something in other words or say with allusions or satire